Specific glycoprotein antigens on the surface of insect and mammalian stages of Trypanosoma cruzi. - Nogueira, N (1982)
Two major surface antigens on Trypanosoma cruzi, the causative agent of Chagas disease, have been described [Nogueira, N., Chaplan, S., Tydings, J., Unkeless, J. & Cohn, Z. (1981) J. Exp. Med. 153, 629-639]. One, a Mr 75,000 glycoprotein (GP), is specific for the culture forms (insect-host stages) of the organisms--epimastigotes and metacyclic trypomastigotes. The other, a Mr 90,000 GP, was found in vertebrate-host stages of the organisms--bloodstream-form trypomastigotes. We now report that these two major surface antigens of T. cruzi seem to be unrelated proteins, as judged by tryptic and chymotryptic peptide analysis. Antibodies were raised in rabbits against epimastigote or trypomastigote proteins which had been immunoprecipitated with human antisera. These trypomastigote and epimastigote protein antisera reacted only with the homologous immunogen, as determined by immunoprecipitation of surface-labeled organisms and by immunofluorescence. The Mr 75,000 GP is detected only in cultured (insect stage) epimastigotes and metacyclic trypomastigotes. The Mr 90,000 GP is only present in bloodstream-form trypomastigotes, amastigotes, and trypomastigotes obtained from infected muscle cells in vitro. Therefore, the insect and vertebrate stages of this species display distinctive surface GPs that can be identified by surface labeling and immunoprecipitation techniques in six strains of T. cruzi (Y, CL, Peru, Colombiana, SF-12, and SF-21) isolated from widely different areas of South America.